Immobilization of Fe(III) complexes of pyridazine derivatives prepared from biosorbents supported on zeolites - Figueiredo, Hugo (2008)
Immobilization of Fe(III) complexes of pyridazine derivatives was achieved in NaY zeolite, loaded with iron through the action of a robust biosorption mediator consisting of a bacterial biofilm, Arthrobacter viscosus, supported on the zeolite. The objective of this study is the preparation and characterization of new catalytic materials to be used in oxidation reactions under mild conditions. The biosorption of Fe(III) ions was performed starting from aqueous solutions with low concentrations of iron and the highest values of biosorption efficiency for Fe(III) were reached at the beginning of the contact period with the sorbents. The Fe(III) biosorption process was compared with the one of Cr(III) under the same experimental conditions, as this latter case has been well characterized. The sample used in the immobilization of Fe(III) complexes of pyridazine derivatives was prepared from an aqueous solution of 100.0 mgFe/L, without the competing effect of other metals. Fe(III) is retained in the zeolite by ion exchange and coordination with two different pyridazine derivative ligands, 3-ethoxy-6-chloropyridazine (A) and 3-piperidino-6-chloropyridazine (B). The resulting materials were fully characterized by different spectroscopic methods (EPR, FTIR and UV–vis), chemical analysis (CA), surface analysis (XRD and SEM) and thermogravimetric (TGA) analysis and the results indicated that the Fe(III) complexes of pyridazine derivatives were effectively immobilized in NaY inside the supercages, without any modifications of the morphology and structure of the zeolite. The EPR spectra of the Fe(III) complexes in Y zeolite show signals at g = 4.3 and 2.3, attributed to Fe(III) species coordinated to pyridazine derivative ligands.